Religious Affiliation and Health Behaviors and Outcomes: Data from the Nashville REACH 2010 Project - Schlundt, David G. (Am J Health Behav, 2008)
OBJECTIVES: Using a large randomly selected community sample, we sought to clarify the relationships among religious involvement, membership in different types of religious groups, health behavior, and health outcomes. METHODS: A survey of Nashville residents (n = 3,014) was conducted for the Nashville REACH 2010 project. The survey included questions about religious affiliation, belief and practice as well as health behaviors and conditions. RESULTS: Bivariate analyses showed negative associations between religious involvement and health behaviors and outcomes along with many differences based on denominational affiliation. After controlling for demographic differences, there was a positive association between religious involvement and several health behaviors and outcomes. After controlling for demographic differences and individual differences in religious involvement, denominational affiliation was no longer associated with any of the health behaviors or health outcome measures. CONCLUSIONS: One should not assume that involvement in any given faith community promotes better health. Rather, each religious group should be approached as a community of people who not only share religious beliefs, but who also have similarities in socioeconomic, ethnic, and cultural background. Health promotion in faith communities must take into account cultural context.